Reframing Global Poverty in Language Education Global: Insights from EFL Textbooks and Teachers in Germany: Book Review - Yunika Triana (Journal of Islamic Studies and Education, 2026)
The book entitled “Reframing Global Poverty in Language Education: Global Insights from EFL Textbooks and Teachers in Germany “ written by Roger Dale Jones examines how global poverty is represented and taught in English as a Foreign Language (EFL) education, particularly through textbooks and classroom practices in Germany. Jones (2026) analyzes how poverty is framed in educational materials and how teachers interpret and teach the topic, using both quantitative and qualitative analysis of textbooks and teacher interviews. The book argues that poverty is often presented in simplified and moralistic ways that overlook its structural complexity, which may shape students’ perceptions of global inequality. The objective of the book is to critically evaluate these representations, identify gaps between educational goals, especially those related to Education for Sustainable Development (ESD) and Global Citizenship Education and classroom practice, and propose more nuanced and interdisciplinary approaches to teaching global poverty in language education.